Margins and market shares : pharmacy incentives for generic substitution - Brekke, Kurt R. (2013)
We study the impact of product margins on pharmacies’ incentive to promote generics instead of brand-names. First, we construct a theoretical model where pharmacies can persuade patients with a brand-name prescription to purchase a generic version instead. We show that pharmacies’ substitution incentives are determined by relative margins and relative patient copayments. Second, we exploit a unique product level panel data set, which contains information on sales and prices at both producer and retail level. In the empirical analysis, we ﬁnd a strong relationship between the margins of brandnames and generics and their market shares. This relationship is stronger for pharmaceuticals under reference pricing rather than coinsurance. In terms of policy implications, our results suggest that pharmacy incentives are crucial for promoting generic sales.